Peran Komunikasi Interpersonal Frontliner dalam Meningkatkan Kepuasan Pelanggan Pengguna LRT Jakarta - Hidayah, Fatma Nur; Kapege, Laode Aharuddin; ., Munawir; Hasyim, Ashar (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This study aims to examine the role of frontliner interpersonal communication in increasing customer satisfaction of Jakarta LRT users. The research method used is descriptive qualitative, with data collection through observation and short interviews. The results showed that clarity of information, friendliness, and responsiveness of frontliners contributed significantly to customer satisfaction. Most respondents were satisfied with the service received Especially related to punctuality, cleanliness, and comfort. However, there are some areas that need improvement, such as addressing rush hour overcrowding and improving accessibility at stations. The conclusion of this study confirms the importance of effective interpersonal communication in building a positive experience and increasing customer loyalty to Jakarta LRT services.